Development of an IoT-Based Smart Scarecrow System with Multi-Sensor Integration for Bird Pest Control in Rice Fields - Ramadhanty, Tarisha; Agustina, Dian Tri; Khusnul Khotimah, Triana Selvia; Ekawati, Ekawati; Zain, Muhammad Yasir; Rachmatullah, Sholeh (ILKOMNIKA, 2026)
This study aims to develop an IoT-based Smart Scarecrow system, an automated bird repellent device that integrates PIR sensors, ultrasonic sensors, an ESP32-CAM camera, LED flashers, ultrasonic buzzers, and a 360° rotation mechanism using a stepper motor. The system is controlled by an ESP32 microcontroller and powered by a solar panel as an independent energy source. The research methodology includes a literature review, system design, hardware and software implementation, laboratory testing, and limited environmental simulation to evaluate system performance. The evaluation focuses on response time, detection accuracy, and operational stability. The results indicate that the system is capable of responding to detected objects in less than 3 seconds, with a real-time visual transmission delay of under 2 seconds. The integration of multiple sensors enhances detection accuracy and reduces false positives. Compared to conventional scarecrow systems, the proposed system demonstrates greater adaptability due to its dynamic response and wider coverage area. However, this study is limited to prototype-scale testing, and further large-scale field validation is required. Overall, the system shows strong potential as an adaptive technological solution for supporting precision agriculture.